Privacy in Canon Law and the relations with national laws of the European Community - INTERGUGLIELMI, ANTONIO (Prawo Kanoniczne, 2018)
With the progressive use of computer systems and with the growing use of media, especially in recent years with the growing spread of internet and social media, the issue of personal data protection has created new needs that require adjustment of canonical regulation. The new issues concerning protection, often made very complex by the difficulty of stifling a phenomenon of "information transmission and therefore also of data" in continuous technological expansion, have made necessary to adapt the rules about privacy protection, to the European Community rules and to the individual countries rules that have to get them and that we will deal with them in our study. Church, which has always been the custodian of memory and history of peoples, through ecclesiastical archives, dioceses, monasteries and even each parish, is required therefore to ensure the protection of the data in its possession, which represent the life of the its churchgoers. In addition, among its fundamental rights, the law of the Church has always recognized the respect of the person, including “the right to the respect of good reputation and confidentiality of each person", which is enshrined in the Code of Canon Law of 1983 in canon 220. Besides, personal data protection involves the connection between the Church's legal order and the laws of the States: in the legislation of many nations, laws that protect the processing of personal data have been promulgated; those rules have to be kept by the National Bishops' Conferences to regulate and adapt the canonical regulation on the treatment of the so-called "sensitive" data to them.